Safety assessment of the process poly recycling, based on starlinger iV+ technology, used to recycle post-consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) (2021)
The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Poly Recycling (EU register number RECYC171). The input is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post-consumer PET containers, with no more than 5% PET from non-food consumer applications. The flakes are dried and crystallised in a reactor, then extruded into pellets which are further crystallised in a second reactor. Crystallised pellets are then preheated in a third reactor and fed to the solid-state polycondensation (SSP) reactor. Having examined the challenge test provided, the Panel concluded that the drying and crystallisation (step 2), extrusion and crystallisation (step 3) and SSP (step 4) are the critical steps that determine the decontamination efficiency of the process. The operating parameters to control the performance of these critical steps are temperature, gas flow and residence time for the drying and crystallisation step; temperature, pressure and residence time for the extrusion and crystallisation step as well as for the SSP step. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long-term storage at room temperature, with or without hotfill. Trays made of this recycled PET are not intended to be used in microwave and conventional ovens and such use is not covered by this evaluation.